Apollonius Rhodius, Herodotus and Historiography - Morrison, A. D. (Cambridge University Press, 2020)
Cover -- Half-title -- Title page -- Copyright information -- Dedication -- Contents -- Preface -- Abbreviations -- Introduction -- Apollonius and Herodotus -- History and Fiction -- Intertexts and Readers -- The Shape of the Argument: History and Politics -- Chapter 1 Receiving Herodotus -- Herodotus and Historiography: The Critical Perspective -- The Herodotean Thought-World -- Panhellenic and Local Perspectives -- Conclusion -- Chapter 2 Creating Authorities -- The Historiographical Mode -- Herodotus as Historiographical Modello-Codice -- What Needs to Be In: Historical Obligation and Apollonius -- Truth and the Limits of Knowledge -- The Past Is a Foreign Country . . . -- Conclusion -- Chapter 3 Explaining the Past -- Introduction -- Explaining Origins and Causes -- Explaining Motivations -- Conclusions -- Chapter 4 Telling Stories -- Introduction -- Herodotean Beginnings -- Herodotean Places -- Lemnos -- Lake Tritonis -- Thera -- Thessaly -- Conclusion -- Chapter 5 Greeks and Non-Greeks -- Introduction -- Greek Worlds -- Home and Abroad -- Egyptians and Otherness -- Persians and Colchians -- Conclusion -- Chapter 6 Kings and Leaders -- Introduction -- Hellenistic Kings and Kingship Ideology -- Exemplary Kings? -- The Problematic of Monarchy -- Kings in Herodotus and Apollonius -- Violence and Power -- Straight Justice -- Conclusion -- Conclusions and Consequences -- Select Bibliography -- Index of Subjects -- Index of Passages.